Implementasi Steganografi Menggunakan Algoritma Diversity Pada Citra Digital - Dodi Siregar; Roji Ramadhani; Yunita Sari Siregar (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2018)
Providing security and confidentiality to information is very important when exchanging information though a communication network. It is intended that the information sent by the sender can be fully accepted by the recipient without interference from parties who are not interested in the information. Steganography techniques can be used to secure secret massages. Steganography is a method for hiding information on a media. Can be in the form of image, sound or video media. The most important aspect of steganography is the level security in hiding information, which refers to how much the third party is unable to detect hidden information. The goal is to avoid suspicion. Steganography commonly used is the hiding of text information on image media. The method used is Diversity. From the results of the trial, it is known that with Diversity insertion and extraction of massages can be done well.